2017
DOI: 10.3341/kjo.2017.31.2.115
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Intravitreal Dexamethasone Implants for Treatment of Refractory Diabetic Macular Edema

Abstract: PurposeTo evaluate the safety and efficacy of intravitreal dexamethasone (IVD) implants in eyes with diabetic macular edema that did not respond to previous treatment.MethodsWe included 46 eyes of 46 patients in this retrospective study. Each month, we recorded patient visual acuity with logarithm of the minimum angle of resolution using the Early Treatment Diabetic Retinopathy Study chart, central macular thickness measurements with optical coherence tomography, intraocular pressure (IOP), and posttreatment c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 30 publications
4
10
0
Order By: Relevance
“…Moreover, topical antiglaucoma medication required in five (4.9%) eyes in the sixth month after the injection. While Kim et al (9), Unsal et al (21), and Kaldirim et al (22) reported IOP elevation in 8.6%, 17.3%, and 11.4% patients after a single dose of IDI injection, Dutra Medeiros et al did not report a significant IOP elevation in 58 patients after a single dose of IDI injection (10). MEAD study reported IOP elevation in 38.1% eyes receiving anti-VEGF therapy and IDI injection for a mean of 4.1 times during 3 years (23).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, topical antiglaucoma medication required in five (4.9%) eyes in the sixth month after the injection. While Kim et al (9), Unsal et al (21), and Kaldirim et al (22) reported IOP elevation in 8.6%, 17.3%, and 11.4% patients after a single dose of IDI injection, Dutra Medeiros et al did not report a significant IOP elevation in 58 patients after a single dose of IDI injection (10). MEAD study reported IOP elevation in 38.1% eyes receiving anti-VEGF therapy and IDI injection for a mean of 4.1 times during 3 years (23).…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, they also reported that 48.9% of the eyes received additional treatment with anti-VEGF or DEX implants. Unsal et al [ 15 ], investigated the efficacy of intravitreal DEX implants in 46 eyes with DME that were unresponsive to previous treatments and reported that BCVA improved significantly in the first 4 months, and CMT decreased significantly in the first 3 months. In a recent meta-analysis of 3,859 patients from 15 studies, intravitreal DEX implant was found to be associated with significant mean improvement in BCVA in patients with DME who have a suboptimal response to anti-VEGF therapy [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutics employed in the reviewed hydrogel devices include an anti-inflammatory corticosteroid, dexamethasone and monoclonal antibodies ranibizumab and bevacizumab and antibody fragment aflibercept (Table 3). Dexamethasone has been used in IVT for the treatment of uveitis [13] and macular edema [59]. Despite the success of the use of steroidal compounds for the aforementioned conditions, the use of corticosteroids in the ocular setting, is marred by the fact that it, as a steroidal compound, might produce unwanted side effects as it is known to induce side effects in many systems.…”
Section: Therapeutics Of Injectable Ivt Hydrogel Implantsmentioning
confidence: 99%